A Review on Cancelable Biometrics - Kanagalakshmi, K; Priya, K. Lakshmi (International Journal of Computer Sciences and Engineering, 2025)
The Cancelable biometrics is a recent development in biometrics based authentication and identification system. In order to avoid the theft of biometric patterns and to improve the security, it is necessary to adopt non- invertible and cancellable biometric templates. There are some methods with Cancelable and irrevocable nature. This paper is aimed to review the literature on the cancelable biometrics template generation methods. Iris biometric has been considered particularly for the further progress based on the methods of from review